Attenuated mRNA expression of inflammatory mediators in neonatal rat lung following lipopolysaccharide treatment - Zhou H; Wiedinger K; Le Rouzic V (Dove Medical Press, 2012)
Valerie Le Rouzic, Kari Wiedinger, Heping ZhouDepartment of Biological Sciences, Seton Hall University, South Orange, NJ, USAAbstract: Neonates are known to exhibit increased susceptibility to bacterial and viral infections and increasing evidence demonstrates that the increased susceptibility is related to their attenuated immune response to infections. The lung is equipped with an innate defense system involving both cellular and humoral mediators. The present study was performed to characterize the expression of inflammatory mediators in the lung of neonatal rats in comparison with older animals. Rats at postnatal day 1 (P1), P21, and P70 were treated with saline or 0.25 mg/kg lipopolysaccharide (LPS) via intraperitoneal injection. Two hours later, animals were sacrificed and the transcriptional response of key inflammatory mediators and enzyme activity of myeloperoxidase (MPO) in the lung of these animals were examined. LPS-induced messenger RNA (mRNA) expression of pro-inflammatory cytokines, namely interleukin (IL)-1β, IL-6, and tumor necrosis factor-α, anti-inflammatory cytokines, namely IL-10 and IL-1 receptor antagonist (IL-1ra), and chemokines, namely macrophage inflammatory protein (MIP)-1β, MIP-2, and monocyte chemotactic protein-1, in P1 lung was much reduced compared to that in P21 and P70 animals at 2 hours postinjection. These data suggest that LPS-induced transcriptional response of cytokines and chemokines was much reduced in P1 lung even though the protein levels of these genes were not ascertained and mRNA levels of these genes may not reflect their final protein levels. MPO activity in LPS-treated P1 lung was also significantly attenuated compared to that in LPS-treated P70 lung, suggesting impaired neutrophil infiltration in P1 lung at 2 hours following LPS treatment. In parallel, the baseline mRNA expression of LPS-binding protein (LBP) in P1 lung was much lower than that in P21 and P70 lungs. While the protein level of LBP was not examined and the mRNA level of LBP may not reflect its final protein level, the reduced transcriptional response of cytokines and chemokines in P1 lung at 2 hours following LPS treatment may be attributed to lower LBP expression in P1 lung as compared to P21 and P70 lungs.Keywords: innate immunity, lung, LPS, development, inflammatory mediators